The Other Pascals : The Philosophy of Jacqueline Pascal, Gilberte Pascal Périer, and Marguerite Périer - Conley, John J. (Book collections on Project MUSE., 2019)
"In The Other Pascals, Conley argues that Jacqueline Pascal, Gilberte Pascal Perier, and Marguerite Perier each developed a distinctive variant of the neo-Augustinian philosophy which functioned as their family's intellectual creed, and which most people know through their brother/uncle, Blaise. Jacqueline's mystical theology, with its acute apophatic sense of God's alterity, contrasts with her sister Gilberte's sober, pragmatic approach. Gilberte's Augustinianism, which downplays the conflicts within and without the Port-Royal circle, contrasts with her daughter Marguerite's accounts of the Pascal family, which highlights the conflicts as opportunities for the exercise of heroic virtue on behalf of the Augustinian theory of grace. Each had philosophical concerns independent of the thought of their brother. Both Jacqueline and Gilberte sketched their own Augustinian philosophy of education. Marguerite's ecclesiology, with its insistence on ecclesiastical fallibility even in matters of faith and morals, reflects the preoccupations of a later Jansenist generation. All three express a gendered concern about the rights of women to receive a serious theological education in the Augustinian mode and to intervene publicly in the ecclesiastical and political disputes of the age. While many studies of Blaise Pascal have noted the complex influence of Jacqueline and Gilberte Pascal upon him, this influence is usually seen as more emotive and religious than intellectual in nature. In this close-knit familial trio, Jacqueline and Gilberte often emerge as the caregivers, nurses, disciples, memorialists, and sparring partners of Blaise. Inevitably, Gilberte's biography of Blaise is included in any edition of Blaise Pascal's collected works"--